Laser desorption/ionization (LDI MS) and thermoprogrammed desorption mass spectrometry (TPD MS) of Europium(III) coordination compound with n-{bis[methyl(Phenyl)amino]phosphorYl}-benzenesulfoneamide - O. V. Severinovskaya; A. V. Mischanchuk; V. A. Trush; A. Yu. Prytula; V. M. Amirkhanov; V. A. Pokrovskiy (Хімія, фізика та технологія поверхні)
The coordination compound EuL3Phen (where L– = N-{bis[methyl(phenyl)amino]phosphoryl}-benzenesulfoneamidate anion) has been synthesized and studied by laser-desorption and temperature-programmed mass spectrometry in the condensed phase and on the surface of a standard metal substrate. The temperature dependence of the main mass spectrum components in the method of temperature-programmed desorption mass spectrometry (TPD MS) is defined and interpreted, components of the laser desorption/ionization (LDI) mass spectrum of the synthesized substance have been identified. A comparative analysis of mass spectra obtained by both methods for the studied coordination compound has been carried out. A possibility of both mass spectrometric methods using for the investigation of metal-containing polymer components is discussed.